Georgia Architectural and Historic Properties Survey of 800 Nardo St., Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
eorgia Architectural and Historic Properties Survey of 800 Nardo St., Valdosta, Ga., December 1980. 1 story L-shaped clapboard sided house with gabled roof. Shed porch held up by square posts. Interior chimney. Double hung sash windows with 6/6 and 9/9 lights. Transom and sidelights around door. Fair condition. Set on brick piers. Date of Construction: App. 1910-1920. Typical vernacular house. Not significant in terms of a N.R. district. Too many modern buildings in the area.
Georgia Architectural and Historic Properties Survey of 800 Nardo St., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 78.1 MB (81,991,690 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)